Integrated Digital Sphygmomanometer for Simultaneous Blood Pressure and Body Temperature Monitoring - Aulia, Farahun Nisa; Pudji, Andjar; Sumber, Sumber (Jurnal Teknokes, 2024)
Hypertension is a condition when the blood pressure against the artery walls is too high. High blood pressure can occur because of the patient's temperature, because the higher the patient's body temperature the higher the blood pressure. Therefore, body temperature must be detected before measuring blood pressure in patients. These Digital Tension and Body Temperature parameters are usually still used separately. Because of that, we had the idea to make these two parameters into one unit to facilitate health monitoring. The design of this tool uses the MPX5050GP sensor as a blood pressure detector, the MLX90614 sensor as a body temperature detector and the two sensors are connected directly to the Arduino UNO microcontroller to be processed and later displayed on the Nextion LCD later. The measurement results with the MPX5050GP and MLX9061 showed that the largest systolic error was 2.23% and the smallest was 0.53%. The biggest diastole error was 4.69% and the smallest was 1.79%. The biggest body temperature error is 1.65% and the smallest is 0.45%.